2012
DOI: 10.5505/1304.7361.2012.50480
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic treatment in patients with acute extremity trauma and effect of training

Abstract: SUMMARY Objectives Studies indicate that emergency physicians (EP) under-evaluate and undertreat the pain experienced by their patients. The objective of this study was to investigate how EPs treat pain in adult patients with limb trauma and to determine if their behavior could be affected by training in the short-term. Methods All consecutive adult patients admitted to the university-based emergency department (ED) within two months ÖZET AmaçÇeşitli çalışmalarda acil hekimlerinin genellikle hastaların ağrısın… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…1,2 In our study, the rate of applying multimodal analgesia was 71.6%, which is between 6.6% and 42.8% of trauma patients in the literature. 6,10,11 The published guidelines stated that appropriate multimodal anal-gesia techniques should be applied to the patient in acute pain. 4,9,12,13 Studies have shown that multimodal analgesia reduces pain, the amount of opioid consumption, and severe the side effects such as respiratory depression.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In our study, the rate of applying multimodal analgesia was 71.6%, which is between 6.6% and 42.8% of trauma patients in the literature. 6,10,11 The published guidelines stated that appropriate multimodal anal-gesia techniques should be applied to the patient in acute pain. 4,9,12,13 Studies have shown that multimodal analgesia reduces pain, the amount of opioid consumption, and severe the side effects such as respiratory depression.…”
Section: Discussionmentioning
confidence: 99%